Efektivitas Penggunaan Aplikasi Qreatif Edukatif Perubahan Wujud Benda terhadap Hasil Belajar Siswa Sekolah Dasar - Riana, Nuryatin Dina; Yulianto, Sigit (Paedagogie, 2026)
The use of technology-based learning media plays an important role in improving the quality of learning and learning outcomes of elementary school students. Interactive learning media can help students understand the concept of changing the form of objects in a more concrete and interesting way. This study aims to find out the differences in student learning outcomes before and after using the Educational Qreatif Application for Changes in the Shape of Things, the difference in learning outcomes between students who use the application and those who do not use the application, and determine the effectiveness of using the application in improving student learning outcomes. This study uses a quantitative approach with a quasi experimental type and a Nonequivalent Control Group Design design. The research sample amounted to 50 grade IV students consisting of 2 class classes, each class amounted to 25 students. Data was collected through pretest and posttest, then analyzed using paired sample t-test, independent sample t-test, and N-Gain test with the help of SPSS. The results showed a significant difference in learning outcomes, as well as an N-Gain value of 0.6871 with a moderate category and a fairly effective percentage. It can be concluded that the use of the Educational Qreatif Application for Changes in the Shape of Objects is quite effective in improving the learning outcomes of elementary school students.